Spike encoding mechanisms in the sound localization pathway - Marsalek, Petr; Kofranek, Jiri (Bio Systems, 2005)
Two distinct neural circuits calculate the direction of incoming sound in mammals. Lower frequency sounds are processed in the medial superior olive (MSO) and higher frequencies are processed in the lateral superior olive (LSO); together they constitute the superior olivary complex. We show that the spike generation mechanisms of coincidence detection (CD) are employed in both these branches of sound localization pathway. Our description uses the concepts of probabilistic spike generation and spike timing jitter. We explain the notch in sound localization sensitivity described in human psychophysics. We estimate the processing time in the superior olivary complex and discuss possible spike processing mechanisms. Among them, we distinguish between the excitatory coincidence detection (ECD) and the inhibitory coincidence detection (ICD). We compare the latter to the mechanism of firing rate subtraction traditionally attributed to the lateral superior olive.
Keywords: modely neurologické; Sound Localization; Models, Neurological; akční potenciály; lokalizace zvuku; Action Potentials